INFLUENCE DE DEUX REGIMES DE CONTRACTION MUSCULAIRE SUR CERTAINS PARAMETRES PHYSIOLOGIQUES, MORPHOLOGIQUES ET SUR LA PERFORMANCE SPORTIVE. (NAGEURS 15 - 18 ANS) (Cas de contraction Dynamique et Isométrique) - GHRICI HOUARI (My University, 2012)
Our research is based on a study comparing two methods of muscle contraction, one is static and the other is a dynamic production of movement. The objective of this study is to implement training program on a team of young swimmers, gender confused and with an age ranging between 15 and 18 and measure the effect of each regime on muscle contraction the parameters studied (Morphological, physiological, athletic performance). The number of swimmers divided into two groups, one group that will pursue a program to build muscle in isometric contraction method, and the other using a dynamic program of contraction with a drive into the water while the common workforce. This comparison study confirm the method of muscle contraction that has the greatest impact on the parameters studied. Conclusion: After a training program implemented over a period that exceeds four months we got to the results or differences that may exist are not significant for all statistical analysis study.
Keywords: Methods of muscle contraction (dynamic) methods of muscle contraction (isometric) physiological parameters, the morphological parameters, sports performance, swimmers from 15 to 18 years.